Efficacy of Ozone and Other Alternative Intrauterine Therapies in Infectious Repeat Breeder Cows. - Ganpatrao, Sawale Abhinay; Markandeya , Niteen Manmohanrao (The Indian Journal of Animal Reproduction, 2023)
The study was undertaken to evaluate the therapeutic efficacy of Ozone, E. Coli LPS, Autologous plasma, Neem oil, and Lugol’s iodine in 100 infectious repeat breeder cows. The animals were divided in 5 different groups viz. Group-I, Group-II, Group-III, Group-IV and Group-V treated with Ozone @ 55µg/ml in 60ml distilled water, E. Coli LPS @100mcg in 30 ml sterile PBS, Autologous plasma @ 30 ml, Neem oil @ 10µg/ml in 30 ml distilled water, Lugol’s iodine 1:25 in 30ml normal saline, intrauterine route in 20 cases, respectively, Group-V of 20 animals was kept as control. AI was done in recovered cases. On follow up, recovery rate in treatment group were found as 75.00, 80.00, 65.00, 75.00 and 50.00 per cent in groups I to V, respectively. The conception rate was found as 68.42, 73.68, 55.00, 63.15 and 53.33 per cent in cows in Group-I to V, respectively. Pregnancy rate was observed that 65.00, 70.00, 50.00, 60.00 and 40.00 per cent cows from groups I to V, respectively. On conclusion, infectious repeat breeder cows treated with E. Coli LPS showed highest recovery rate, conception rate and pregnancy rate than the other treatment groups in this research study.